Problem of Perception of the Verbal Component of Modern RussianLanguage Infographics (Proceedings of Southern Federal University. Philology, 2019)
Margarita M. Makhrova (Vladimir, Russian Federation)Infographics is an interesting phenomenon of the information and communication space of the XXI century. Modern Russian-language infographics is a synthesis of visual and verbal components and in a compressed form conveys a large amount of information to the addressee. Objective: to find out how the textual component of the infographic is perceived, which words and phrases help to understand the content, which remains incomprehensible, and based on the data obtained, formulate recommendations for drafting competent and current textual content of Russian-language infographics.When compiling an infographic, it should be determined what kind a specific example will be related to. Depending on this, it is made up the lexical and morphological content.Key words: infographics, verbal component, perception, addressee, author, communication, survey, research, classification, text content.DOI 10.23683/1995-0640-2019-3-55-60